2013
DOI: 10.1007/s00277-013-1712-6
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of myelodysplastic syndromes in Western Greece is increasing

Abstract: Descriptive epidemiology of the myelodysplastic syndromes (MDS) is always interesting and may reveal time-dependent and geographical variations, as well as occupational exposure. Epidemiological data in Greece are not available by now. We have collected and analyzed medical records of all patients with a documented diagnosis of MDS, performed by an expert hematologist and/or hematopathologist, in the geographical area of Western Greece, during the 20-year period, defined between 1990 and 2009. We have then cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
24
6
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 22 publications
12
24
6
3
Order By: Relevance
“…MDS is generally considered a preleukemic disorder and is prevalent in elder individuals in western world [5]. However, median age at diagnosis in our study was younger which concurs with other studies done in Asia [1][2][3][4][6][7][8] as compared to the studies from west with higher median age in MDS (Greece, Germany, Poland) [10,14,15]. In our study we observed male predominance which is universally seen in this disorder [1][2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…MDS is generally considered a preleukemic disorder and is prevalent in elder individuals in western world [5]. However, median age at diagnosis in our study was younger which concurs with other studies done in Asia [1][2][3][4][6][7][8] as compared to the studies from west with higher median age in MDS (Greece, Germany, Poland) [10,14,15]. In our study we observed male predominance which is universally seen in this disorder [1][2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 63%
“…In our study we observed male predominance which is universally seen in this disorder [1][2][3][4][5][6][7][8]. However, male to female ratio was 3:1 which is slightly higher as compared to previous studies [1-4, 6, 7] and somewhat comparable to what has been observed in Greece [10]. The possible explanation of gender in our region could be low literacy rate in our country and male predominant society where females seek medical attention less frequently.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…This finding was in contrast to some extensive studies of the epidemiology of different subtypes of MDS, which indicate that RA, RARS, RAEB, and RAEBt are the most common subtypes, respectively. [17,36] There was a relatively poor prognosis in these patients. Only 5 patients responded to treatment, among which 2 cases were treated with imatinib.…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…We have conducted a retrospective epidemiological study on the incidence of MDS in this region, during the period 1990-2009, which revealed an increasing trend for diagnosing an MDS. This was mainly attributed to an increase of RA and RARS, whereas the incidence of RAEB and CMML remained rather stable over the study period [3]. The observed increasing trend in the incidence of MDS in Western Greece led us to search for potential risk factors in this particular region.…”
Section: Introductionmentioning
confidence: 99%